ASSESSMENT OF THE ATTITUDE OF INTENSIVE CARE UNITS NURSES OF THE DIMENSIONS OF A SAFETY CULTURE - Mamčenkovaitė, Evelina; Spirgienė, Lina (Slauga. Mokslas ir praktika, 2023)
To assess intensive care unit nurse’s attitude towards patient safety dimensions.Methods. The study was conducted at two hospitals, from 2022 April till June in Intensive Care Units. 156 nurses participated in the study. The questionnaire was made by authors according to the „Manchester Patient Safety Framework. Acute” literature.Results. Nurses with a university education agreed more often than those with a non-university education that their department takes a responsible approach to patient safety issues (respectively, n=52; 96.3% and n=93; 95.9%), p=0.05, that departments have a correct understanding of why it is necessary to report adverse patient safety events (respectively, n=51; 80.0% and n=80; 51.0%), p=0.04.Non-university-educated nurses indicated more often than university-educated nurses that their department constantly assesses risks related to patient safety and looks for ways to improve quality (respectively, n=92; 93.9% n=43; 79.6%), p=0.02 that adverse patient safety events are not seen as an opportunity to blame the nurse or other staff (respectively, n=62; 64.6% and n=25; 46.3%,), p=0.04. Nurses with a non-university education more often agreed that there is no prevailing culture of blame in the department (respectively, n=65; 67.7% n=25; 46.3%), p=0.02, more often report potential adverse events (respectively, n =26; 48.1% and n=58, 61.1%), p=0.01, than nurses with university education.Conclusions. Critical care and intensive care nurses pay sufficient attention to patient safety, system error and individual responsibility, and adverse event recording and best practice dimensions. However, in the opinion of university-educated nurses, risks related to patient safety are still not sufficiently assessed in the workplace and ways to improve quality are sought, there is a lack of safety culture.
Keywords: patient safety; intensive care units’ nurses; safety culture